2012
DOI: 10.1007/s12603-011-0347-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and psycho-functional status in elderly patients with Alzheimer's disease

Abstract: The psycho-functional decline of patients with AD is related to body composition variations, with a relative increase of fat mass with respect to the muscle component. The BIVA technique distinguished patients from controls and patients with different levels of cognitive decline. Therefore, it is a suitable tool for the screening and monitoring of nutritional status in Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 34 publications
6
46
1
4
Order By: Relevance
“…Given that Xc is directly related to the amount of soft tissue structures, and that R is inversely related to the ICW and ECW, this finding clearly indicates an alteration in BCM with a comparable amount of total body water in the groups, as can be observed in Figure 1. Our findings are in agreement with previous studies performed with BIVA, in which patterns in patients with AD were also characterized by a reduction in Xc/H values with preserved R/H [36,37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Given that Xc is directly related to the amount of soft tissue structures, and that R is inversely related to the ICW and ECW, this finding clearly indicates an alteration in BCM with a comparable amount of total body water in the groups, as can be observed in Figure 1. Our findings are in agreement with previous studies performed with BIVA, in which patterns in patients with AD were also characterized by a reduction in Xc/H values with preserved R/H [36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the BCM can also be defined as the FFM minus the extracellular mass (i.e., the bone mineral, and ECW), and consequently, a depleted level of BCM in the DG with respect to the CG is plausible even without significant differences in FFM between the groups. These findings suggest, in turn, a change in the FFM composition in the DG with respect to the CG, characterized by a relative increase in ECW with respect to ICW that can be interpreted as a low number of cells per unit volume [36]. This in turn could be compatible with a greater loss of skeletal muscle mass (SMM) because the decrease in SMM has been shown to be greater than that of the non-muscle lean (organ) mass in older adults [39,40].…”
Section: Discussionmentioning
confidence: 88%
“…Given that our sample was selected to have no serious diseases and the statistical modeling has controlled for disease history, this small proportion of the sample could have suffered from malnutrition, as indicated by their relatively lowest CBMI. The finding was consistent with studies that examined the relation of nutrition to cognitive functions in the older adults [15,[18][19][20]29] and findings that overweight is unnecessarily related to impaired CF [30]. There are two possible explanations for their underweight.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies examined the nutritional status of elderly either in term of BMI or measures of nutrition and found that those with moderate or severe cognitive impairment also had higher risks of malnutrition [15,[18][19][20] Although it was difficult to determine from these studies, there is good reason to consider that malnutrition caused cognitive impairment, as many nutritional elements are needed in biochemical processes [21].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Saragat (30) showed that there is a strong link among cognitive score, nutritional status and body composition.…”
Section: Nutritional Status and Body Compositionmentioning
confidence: 99%